Pig farm biogas slurry can effectively reduce the pH of saline-alkali soils. Issue 10 (29th April 2023) - Zhu, Yongli; Yuan, Gen; Zhao, Zihui; Tang, Yifan; Li, Pingping; Han, Jiangang
ABSTRACT: Pig farm biogas slurry is being increasingly used as a potent organic fertilizer for sustainable agriculture under circular economy. However, the effect of biogas slurry on soil pH is currently controversial, and the underlying mechanisms especially in saline-alkali soils are not well understood. A saline-alkali soil (pH = 9.2, EC = 2.0 ms/cm) was selected for soil column (0–50 cm) experiments with (BS) and without (CK) addition of pig farm biogas slurry to investigate the soil pH change and its driving factors. Our results show that the soil pH under CK ranged between 9.1 and 9.5 across different soil depths. Compared to CK, the BS-treated soil had lower pH at 0–20 cm depth and higher pH at 20–30 cm depth ( P < 0.01 ). The soil NH 4 + − N concentrations were negatively correlated with pH values under BS ( P < 0.01 ), indicating that the oxidation of ammonium mainly contributed to the decrease of soil pH. Interestingly, the anions, such as Cl −, SO 4 2 − and NO 3 −, were accumulated in the topsoil (0–20 cm) under BS, resulting in the changed correlations of these anions with Na + when compared to the control. FT-IR and 13 C-NMR spectra uncovered that carboxyl, amide C, and total alkyl C groups may be responsible for reducing pH of the saline-alkali soil tested. The soil surface morphology confirmed a much tighter granular aggregate microstructure when mixing the biogas slurry with the soil. Overall, we concluded that from the perspective of soil pH, the utilization of biogas slurry for improving saline-alkali soil is feasible and sustainable. GRAPHICAL ABSTRACT: UF0001